Ontologia e essência humana em Lukács - Silva Júnior, Antonio Gonzaga da (2021)
The present work aims to investigate the conception of the category of human essence present in the posthumous work of the Hungarian Marxist philosopher Georg Lukács entitled Towards the Ontology of Social Being I and II. To do so, we initially conduct an examination of Lukács' materialist ontological conception of the world. Then, we carry out an analytical prospection of the economic, historical-social, ideo-political and cultural context of the main elaborations of ontological conceptions in the historical process of humanity, highlighting its main formulators. Finally, we turn to the analysis of the category of human essence, its genesis, formation and development.